Strategi Guru Pendidikan Agama Islam (PAI) Dalam Menanamkan Nilai Religius Siswa Di Madrasah Ibtidaiyah Negeri 5 Kota Banda Aceh - Ismail, Ismaidar; Zamroni, M Afif (Program Studi Pendidikan Agama Islam, 2023)
This research examines the principal's strategy for implementing inclusive education at SMKN 1 Cikalongkulon Cianjur and identifies Madrasah Ibtidaiyah (MI) Negeri 5 Banda Aceh City. Instilling religious values ??is very important amidst the influence of globalization and promiscuity, which can erode religious values. The approach used is descriptive qualitative with field research type. Data was collected through participant observation, unstructured interviews, and documentation. The research subjects consisted of madrasa heads, PAI teachers, and students. Data analysis uses the Miles and Huberman model, including data reduction, presentation, and conclusion. The validity of the data is obtained through source triangulation and technical triangulation. The research results show that the strategies used by PAI teachers at Madrasah Ibtidaiyah (MI) Negeri 5 Banda Aceh City in instilling religious values ??in students gave positive results. Students become more understanding and confident in the values ??of aqidah, worship, and morals in Islam and try to practice them daily. This will, of course, have an impact on the formation of students' better character and personality by the teachings of the Islamic religion. This research contributes to the development of educational science, especially in efforts to produce a generation of faith, piety, and noble character by national education goals